"Aus meiner Familie weiß niemand, dass ich putzen gehe". Informelle Erwerbsarbeit in Privathaushalten: Informelle Erwerbsarbeit in Privathaushalten - Gather, Claudia (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
In the last twenty years it has become more common in Germany for middle class households to hire a domestic worker informally for some hours a week to do the rough and dirty cleaning tasks. About two million people are working in this sector, a substantial part of them are undocumented migrant worker, but nobody knows for sure. In this paper, case studies of the people doing this work are presented, and political efforts to transform informal domestic work into regular jobs are addressed. These efforts failed, because too little is known about the women doing these jobs. Thus there is a need for further research.